Orthostatic Challenge Shifts the Hemostatic System of Patients Recovered from Stroke toward Hypercoagulability - Cvirn, Gerhard; Kneihsl, Markus; Rossmann, Christine; Paar, Margret; Gattringer, Thomas; Schlagenhauf, Axel; Leschnik, Bettina; Koestenberger, Martin; Tafeit, Erwin; Reibnegger, Gilbert; Trozic, Irhad; Rössler, Andreas; et al. (Frontiers in Physiology, 2017)
Aims: The objective of our study was to assess the effects of orthostatic challenge on the coagulation system in patients with a history of thromboembolic events and to assess how they compared with age-matched healthy subjects. Methods: Twenty-two patients with histories of ischemic stroke and 22 healthy age-matched subjects performed a sit-to-stand test. Blood was collected prior to- and at the end of- standing in the upright position for 6 minutes. Haemostatic profiling was performed by determining thrombelastometry and calibrated automated thrombogram values, indices of thrombin generation, standard coagulation times, markers of endothelial activation, plasma levels of coagulation factors and copeptin, and hematocrit. Results: Orthostatic challenge caused a significant endothelial and coagulation activation in patients (Group 1) and healthy subjects (Group 2): Plasma levels of prothrombin fragment F1+2 were increased by approximately 35% and thrombin/antithrombin-complex (TAT) increased fivefold. Several coagulation variables were significantly altered in Group 1 but not in Group 2: Coagulation times (CTs) were significantly shortened and alpha angles, peak rate of thrombin generation (VELINDEX), tissue factor (TF) and copeptin plasma levels were significantly increased (comparison between standing and baseline). Moreover, the shortening of CTs and the rise of copeptin plasma levels were significantly higher in Group 1 vs. Group 2 (comparison between groups). Conclusion: The coagulation system of patients with a history of ischemic stroke can be more easily shifted towards a hypercoagulable state than that of healthy individuals. Attentive and long-term anticoagulant treatment is essential to keep patients from recurrence of vascular events.